Tax, private school fees and state school spending - Luke Sibieta (Institute for Fiscal Studies (IFS), 2023)
The Labour party has proposed a package of policies to remove tax exemptions from private schools. Most importantly in revenue terms, it has proposed levying VAT on private school fees. The revenue raised would then be used to increase state school spending and would be targeted at pupils from disadvantaged backgrounds. In this report, we analyse the likely effects of these proposals on tax revenues and school spending.
Keywords: 330; Education and skills; Government finances and spending; Taxes and benefits; Education spending; Education; Schools; Government spending; Human capital; Public sector; Tax; VA